Chromatic Visions Exploring Colour in Art, Archaeology and Digital Realities, Part II - Ciortan, Irina Mihaela; Ferdani, Daniele; Hardeberg, Jon Yngve; Sotiropoulou, Sophia; Veggi, Manuele; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2026)
This open access book builds upon the conceptual foundations established in the first part, presenting practical methods, tools, and workflows for studying and communicating colour in cultural heritage. Developed within the Horizon Europe project PERCEIVE, this second volume examines how scientific analysis, digital reconstruction, and interactive design can be integrated into reproducible workflows. It documents the operational frameworks, technological infrastructures, and design resources developed to study, model, visualise, and communicate colour change across diverse heritage collections. Structured around three complementary chapters (scientific modelling of colour change, digital tools and services for knowledge sharing, and design resources for interactive experiences) the book presents advanced workflows, AI-assisted methods, FAIR data infrastructures, and participatory exhibition prototypes. Case studies range from ancient polychromy and paintings to textiles, photography, and born-digital art, demonstrating approaches to make colour research accessible and transparent for both specialists and broader audiences. Grounded in principles of care, authenticity, and participation, Chromatic Visions II addresses digital heritage as both a technical and relational practice. The book provides researchers, conservators, curators, designers, and museum professionals with methods and frameworks for interdisciplinary approaches to the digital study and communication of coloured collections.
Methods and Workflows for Colour Change Modelling and Reconstruction -- Tools and Services for Colour Change Analysis and Sharing of Knowledge -- Design Resources to Enhance Access to Coloured Collections through Interactive Experiences.
Accessibility summary: This PDF has been created in accordance with the PDF/UA-1 standard to enhance accessibility, including screen reader support, described non-text content (images, graphs), bookmarks for easy navigation, keyboard-friendly links and forms and searchable, selectable text. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com. Please note that a more accessible version of this eBook is available as ePub.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Computer vision; Color; Vision; Art -- History; Cultural property; Archaeology; Psychodiagnostics; Computer Vision; Vision and Colour Science; Art History; Cultural Heritage; Archaeology and Heritage; Psychological Diagnostics